Public awareness of hepatitis B infection in Turkey as a model of universal effectiveness in health care policy - Gürakar, Merve; Malik, Mohammad; Keskin, Onur; İdilman, Ramazan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: This study aimed to analyze the knowledge and awareness of hepatitis B virus (HBV) infection in an HBV-infected Turkish population as a model for global health care practice and to evaluate potential factors associated with the disease spread and its prevention. Materials and Methods: A cross-sectional survey was conducted in Ankara University School of Medicine, Liver Disease Outpatient Clinic between August 2012 and March 2013. The survey queried sociodemographics, knowledge, and awareness of HBV infection, transmission, and consequences and common practices and behaviors. Results: A total of 181 patients were surveyed (median age=49 years); 91 (51%) had “advanced” education levels (high school, bachelor’s, graduate degree), 108 (60%) had knowledge about HBV infection and transmittance, and 130 (72%) were aware of the ill consequences of HBV infection. Also, 120 (66%) had vaccinated their family members against HBV infection. Participants with knowledge of HBV infection transmittance were more likely to vaccinate their family members compared to unknowledgeable participants (p=0.015). Participants with “advanced” education levels were also more likely to vaccinate family members (p=0.047). Conclusion: Promoting better awareness of HBV and endorsing mass educational interventions may be useful strategies to prevent the spread of HBV infection. Such strategies may be recommended as cost-effective global health care practices in HBV endemic areas.